1994
DOI: 10.1161/01.hyp.23.6.710
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dependency of frequency-stimulated atrial natriuretic peptide secretion.

Abstract: In this study we examined the mechanism whereby atrial natriuretic peptide secretion is increased when the frequency of contraction is raised from 2 to 5 Hz. We tested the hypothesis that calcium plays a significant role in the frequency-stimulated response. Using superfused rat left atria, we found that lowering the superfusate calcium concentration from 1.8 to 0.2 mmol/L abolished the frequency-stimulated atrial natriuretic peptide secretory response. Superfusion with ryanodine (1 /xmol/L), an inhibitor of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
(24 reference statements)
1
13
1
Order By: Relevance
“…Frequencyinduced ANP secretion is associated with the activation of NHE, which results in the increase of [Ca 2ϩ ] i by a reversal of the operation mode of the Na ϩ /Ca 2ϩ exchanger (45). However, pretreatment with L-type Ca 2ϩ channel blocker did not affect ANG-(1-7)-augmented ANP secretion in atria with high pacing.…”
Section: Discussionmentioning
confidence: 91%
“…Frequencyinduced ANP secretion is associated with the activation of NHE, which results in the increase of [Ca 2ϩ ] i by a reversal of the operation mode of the Na ϩ /Ca 2ϩ exchanger (45). However, pretreatment with L-type Ca 2ϩ channel blocker did not affect ANG-(1-7)-augmented ANP secretion in atria with high pacing.…”
Section: Discussionmentioning
confidence: 91%
“…Mechanical stretch in isolated atrial tissues was reported to increase the intracellular Ca 2 + transients and the late duration of the action potentials, which was ascribed to the stretch-induced channel activation and resultant augmentation of the Na + /Ca 2 + -exchanger inward current [21,22]. It has also been proposed that intracellular Ca 2 + plays a critical role in ANP secretion from atrial cells and changes of cytosolic Ca 2 + concentration affect ANP secretion [8,23,24]. Activation of atrial K ATP channels by mechanical stretch may decrease the cytosolic Ca 2 + concentration by abbreviating the action potentials, which is expected to reduce the time for Ca 2 + influx via L-type Ca 2 + channels and to increase the time for Ca 2 + extrusion through the Na + /Ca 2 + -exchange system.…”
Section: Possible Mechanisms Underlying K Atp Channel-mediated Regulamentioning
confidence: 99%
“…Increases in Ca 2ϩ influx via L-type Ca 2ϩ -channel activation by BAY K 8644 increased ANP secretion in perfused heart (24,26), isolated beating atria (28,29), and cultured atrial myocytes (18). Similarly, L-type Ca 2ϩ -channel blockers inhibit ANP secretion in perfused heart (26) and isolate beating atria (28,29) and atrial myocytes (5,18). Increased extracellular Ca 2ϩ also results in an increase in ANP secretion in beating atria (15).…”
Section: ϩmentioning
confidence: 99%